Manajemen Tenaga Kependidikan dalam Upaya Peningkatan Kualitas Layanan di SMAN 4 Mataram - Putu Wiwik Puspa Darmayanti; Nada Sobah; Mohamad Mustari (Lembaga Einstein College (LEC), 2026)
This study aims to analyze the management of educational staff in an effort to improve service quality at SMAN 4 Mataram. The study was conducted due to issues such as the mismatch between staff placement and their competencies, as well as the suboptimal quality of services provided. This research using qualitative method with a case study approach. Data were collected through observation, in-depth interviews, and documentation involving the principal, the sub-coordinator of Administration, educational staff and teachers. The finding indicate that the implementation of educational staff management has not been optimal due to limited competencies, unequal workload distribution, and inconsistent supervision. This study concludes that the improvement of educational service quality is strongly influenced by the effectiveness of educational staff management. Therefore, strategies such as strengthening job needs analysis, continuous training workload structuring, and developing a culture of excellent service need to be implemented systematically and sustainably to enhance service effectiveness at SMAN 4 Mataram